The differences in selected health-related behaviour indicators among women with different educational attainment in Slovenia - Gabrijelčič Blenkuš, Mojca (Zdravstveno varstvo, 2013)
Background: Numerous studies have found significant gender differences in health-related behaviour, while a lower number analyse these differences within the gender. The aim of the article is to analyse the differences in individual health-related behaviour indicators among women from different educational groups in Slovenia. Methods: The analysis is based on the CINDI Health Monitor (2008) survey for Slovenia. The nationally representative sample was chosen using probability sampling and the analysis included 4,237 women aged 25 to 74. The independent variables are: education, in consideration of age, community type, region of residence, the presence of a partner and children and self-perceived social class. The dependent variables are health-related behaviours: nutrition, physical activity, sleeping, stress and care for own health. By comparing averages in health-related behaviour with education and other factors and by classifying participants into homogenous groups, we were able to show differences in health-related behaviour in women with different educational attainment. Results: Individual health-related behaviour indicators show statistically significant differences between groups of women with different educational attainment; however these are neither very distinct nor unambiguous. Women with a higher educational attainment evaluate the majority of the indicators more favourably than women in other educational groups, but differences can also be found within the group of women with a higher educational attainment. The differences in the health-related behaviour of women with a lower educational attainment are relatively blurred. Conclusion: The relatively small differences in health-related behaviour can be partially explained by existing differences within the group of women with a higher educational attainment and the fact that the group of women with the lowest educational attainment does not have the worst health-related behaviour indicators, which affects the greater equality in health-related behaviour. On the other hand, the well-established universal and targeted family and child care policies, which have been implemented in Slovenia for decades, also affect these results.
Keywords: food; izobrazba; neenakost; prehrana; skrb za zdravje; skupni čas spanja; stres; telesna dejavnost; vedenjski slog; woman; zdravje; ženske